Systemic DNA damage responses in aging and diseases. (June 2016) - Ribezzo, Flavia; Shiloh, Yosef; Schumacher, Björn
Abstract: The genome is constantly attacked by a variety of genotoxic insults. The causal role for DNA damage in aging and cancer is exemplified by genetic defects in DNA repair that underlie a broad spectrum of acute and chronic human disorders that are characterized by developmental abnormalities, premature aging, and cancer predisposition. The disease symptoms are typically tissue-specific with uncertain genotype–phenotype correlation. The cellular DNA damage response (DDR) has been extensively investigated ever since yeast geneticists discovered DNA damage checkpoint mechanisms, several decades ago. In recent years, it has become apparent that not only cell-autonomous but also systemic DNA damage responses determine the outcome of genome instability in organisms. Understanding the mechanisms of non-cell-autonomous DNA damage responses will provide important new insights into the role of genome instability in human aging and a host of diseases including cancer and might better explain the complex phenotypes caused by genome instability.